PERAN SEL STELATA HEPATIK PADA SIROSIS HEPATIS - Pattabang, Iola; Wangko, Sunny (JURNAL BIOMEDIK : JBM, 2009)
Abstract: Hepatic stellate cell was firstly described by Carl von Kupffer in 1876 by using glod chloride staining. Stellate cells are found in spaces of Disse, that are located between hepatocytes and sinusoid endothelial cells. The main function of stellate cells is as vitamine A-storing cells. In liver cirrhosis, these stellate cells are activated and become proliferative, fibrogenic, and contractile myofibroblasts. Keywords: hepatic stellate cell, activated, cirrhosis  Abstrak: Sel stelata hepatik pertama kali dideskripsikan oleh Carl Von Kupffer pada tahun 1876 dengan menggunakan metode pewarnaan gold chloride. Sel stelata terletak dalam celah Disse, yaitu celah antara hepatosit dan sel endotel sinusoid. Fungsi utama dari sel stelata ialah menyimpan vitamin A. Pada sirosis hepatis sel stelata akan teraktivasi menjadi miofibroblas yang bersifat proliferatif, fibrogenik dan kontraktil. Kata kunci: sel stelata hepatik, teraktivasi, sirosis